The Effect of Buddleja officinalis Maxim Eye Drops on Morphology and Apoptosis in Lacrimal Gland of Experimental Dry Eye Rabbit Model - Genyan Qin; Yasha Zhou; Jun Peng; Youwei Zhang; Xiaofang Peng; Qinghua Peng; Yijing Yang (Journal of Ophthalmology)
The purpose of this study was to investigate the effects of Buddleja officinalis Maxim eye drops on morphology and apoptosis in lacrimal glands of the experimental dry eye rabbit model. A total of thirty-six male rabbits were divided into six study groups, consisting of the control group and the dry eye rabbit model group (without any treatment), the dry eye rabbit model group treated with testosterone, and the dry eye rabbit model group treated with different concentrations of Buddleja officinalis Maxim eye drops (1.0 mg/ml, 1.5 mg/ml and 3.0 mg/ml). The lacrimal glands were evaluated by hematoxylin-eosin staining and immunohistochemistry. Buddleja officinalis Maxim eye drops can improve the morphological structure of the lacrimal gland in the dry eye model of castrated rabbits. The average optical density values of PI3K, Akt, and caspase-9 protein in the lacrimal gland tissue of the 3 mg/ml Buddleja officinalis Maxim eye drops group were significantly different from those in the model group (P<0.01) and similar to the testosterone control group and the control group (P>0.05). Buddleja officinalis Maxim eye drops can improve the morphological structure of the lacrimal gland in the dry eye model of castrated rabbits.